Risk factors in street food practices in developing countries: A review - Buliyaminu Adegbemiro Alimi (Food Science and Human Wellness)
Street food trading solves major social and economic problems in developing countries through the provision of ready-made meals at relatively inexpensive prices and employment for teeming rural and urban populace along its value chain. However, due to informal nature of the enterprise, the activities of the practitioners are not regulated. This gives ample room for unwholesome practices. The results are the risks such activities pose to the health and safety of practitioners along the value chain. This review paper, a summary of literature reports on risk factors in street food trade in developing countries and recommended safety intervention, is written with the hope of providing global baseline for intervention to ensure safe food practices. Adoption of safety approaches that permeates the entire chain of street food business from good agricultural practices through hazard analysis critical control points strategy to good hygiene practices by farmers, vendors and consumers would significantly reduce risks in street food consumption. Above all, active collaboration of all stakeholders toward the strengthening and proper enforcement of public health policies to ensure safe practices and engender safer and healthier society is recommended.